Visfatin and Resveratrol Differentially Regulate the Expression of Thymidylate Synthase to Control the Sensitivity of Human Colorectal Cancer Cells to Capecitabine Cytotoxicity - Kuen-Lin Wu; Ko-Chao Lee; Chia-Kuang Yen; Cheng-Nan Chen; Shun-Fu Chang; Wen-Shih Huang (Life, 2021)
Colorectal cancer (CRC) is a highly lethal malignant cancer. Capecitabine, a 5-fluororacil (5-FU) derivate, is its first-line drug, but the resistance of CRC to capecitabine is still the most challenging factor for curing patients. It has been suggested that thymidylate synthase (TYMS) level might affect the capecitabine efficacy in CRC patients, but the mechanism still needs more elucidation. Obesity is a risk factor for CRC. Recently, a correlation between serum visfatin, an obesity-elicited adipokine, and CRC development has been found. Thus, the aim of present study is to examine the visfatin capacity in TYMS expression and in the development of capecitabine resistance of CRC. Moreover, an attractive natural component, i.e., resveratrol, has been proposed in anticancer therapy and has hence been examined in the present study to see its potential capacity in the alleviation of CRC resistance. Our results found that visfatin significantly reduces the CRC sensitivity to capecitabine by controlling the TYMS expression via p38 signaling and Sp1 transcription factor. Moreover, resveratrol could significantly alleviate the visfatin effect on capecitabine-treated CRC cells. These results provided new insights to understand the capecitabine susceptibility of CRC under a visfatin-containing environment and a possible therapeutic application of resveratrol in CRC patients with obesity.